UV Spectrophotometric Determination of Ziprasidone Hydrochloride in Pure and Pharmaceutical Formulation - CHAUHAN, C.S.; CHOUDHURY, P.K. (Asian Journal of Chemistry, 2010)
Simple and sensitive method has been developed for determination of ziprasidone hydrochloride monohydrate (ZPH) in both pure and pharmaceutical formulation. This method obeys Beer's law in the concentration range of 10-70 μg/mL, exhibiting maximum absorption at 318 nm. In this method no interference from the common pharmaceutical excipients was observed.